2016
DOI: 10.21037/gs.2016.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Langerhans cell histiocytosis and papillary thyroid carcinoma

Abstract: A 27-year-old female, married with two children, presented to our clinic with a 1-year history of thyroid swelling and pressure symptoms on lying backward and bilateral cervical lymphadenopathy. The patient was a known case of panhypopituitarism for 5 years. Comprehensive patient evaluation including FNAC with papillary thyroid cancer result then she underwent total thyroidectomy and bilateral neck dissection and final histologic examination confirmed papillary thyroid carcinoma in the background of lymphocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…FNA from thyroid in this patient showed features of PTC. On histopathological examination of the thyroid, there was evidence of LCH in addition to PTC, which was confirmed by immunohistochemistry . Ceyran et al reported a similar case in a 37‐year‐old man who presented with a thyroid swelling and lymphadenopathy.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…FNA from thyroid in this patient showed features of PTC. On histopathological examination of the thyroid, there was evidence of LCH in addition to PTC, which was confirmed by immunohistochemistry . Ceyran et al reported a similar case in a 37‐year‐old man who presented with a thyroid swelling and lymphadenopathy.…”
Section: Discussionmentioning
confidence: 81%
“…Coexistence of LCH and PTC in thyroid is very rare and a few case reports have been documented in literature. Rajab et al reported a similar case in a 27‐year‐old woman who presented with neck swelling and symptoms of hypothyroidism and diabetes insipidus. FNA from thyroid in this patient showed features of PTC.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Its association with PTC is also extremely rare, with only few case reports available in the literature [18]. Table 1 represents the cases of synchronous papillary thyroid carcinoma and Langerhans cell histiocytosis co-existing in the thyroid gland [1, 2, 716]. Herein, we report a case of co-existing PTC and LCH in the thyroid gland with detected BRAF V600E and V600K mutations respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the close international collaboration we are presenting in this issue 12 reports from leading experts in the field focused on selected hot topics in endocrine surgery: intraoperative neural monitoring (IONM) in thyroid surgery (1,2), safety of energy based devices (EBD) for hemostasis in thyroid surgery (3), utility of BRAF V600E mutation for prognostication of papillary thyroid cancer (PTC) recurrence (4), rare cases of PTC associated with thyroid Langerhans cell histiocytosis (5), management of thyroid cancer with tracheal invasion (6), utility of indocyanine green-enhanced fluorescence to assess parathyroid perfusion during thyroidectomy (7), value of iPTH assay for early prognostication of postoperative hypocalcemia (8), risk factors for perioperative hemodynamic instability in patients undergoing laparoscopic adrenalectomy for pheochromocytoma (9), utility of laparoscopic sleeve gastrectomy (LSG) for the treatment of diabetes mellitus type 2 (10), innovative solutions in bariatric surgery (11), including new endoscopic procedures for diabetes mellitus type 2 and obesity treatment (12).…”
mentioning
confidence: 99%